Zwischen Konsens und Entgrenzung: Zur Transkulturalität des kommunikativen Handelns - Schippel, Larisa (chronotopos – A Journal of Translation History, 2020)
This contribution is Larisa Schippel’s inaugural lecture for the professorship of Transcultural Communication, given at the Hieronymus Day at the Centre for Translation Studies at the University of Vienna on October 4, 2011. The translation was drafted shortly thereafter. The text has not been published yet, but is reproduced here in its original form, because the editors think it includes noteworthy considerations for a transcultural perspective of translation phenomena.